Atmospheric energetics over India during drought and normal monsoons - RAO, G. APPA (MAUSAM, 1981)
Energetics of the atmosphere during a drought and normal southwest monsoons over India based on upper air data have been computed. The parameters considered are sensible heat, latent heat, kinetic energy and angular momentum. The mean and eddy components due to meridional circulation are separated and the differences between the two contrasting years are highlighted. The present results are compared with the earlier ones obtained over India.